Hierarchical optofluidic microreactor for water purification using an array of TiO2 nanostructures - Kim, Hyejeong; Kwon, Hyunah; Song, Ryungeun; Shin, Seonghun; Ham, So-Young; Park, Hee-Deung; Lee, Jinkee; Fischer, Peer; Bodenschatz, Eberhard (Clean water, 2022)
Clean water for human consumption is, in many places, a scarce resource, and efficient schemes to purify water are in great demand. Here, we describe a method to dramatically increase the efficiency of a photocatalytic water purification microreactor. Our hierarchical optofluidic microreactor combines the advantages of a nanostructured photocatalyst with light harvesting by base substrates, together with a herringbone micromixer for the enhanced transport of reactants. The herringbone micromixer further improves the reaction efficiency of the nanostructured photocatalyst by generating counter-rotating vortices along the flow direction. In addition, the use of metal-based substrates underneath the nanostructured catalyst increases the purification capacity by improving the light-harvesting efficiency. The photocatalyst is grown from TiO2 as a nanohelix film, which exhibits a large surface-to-volume ratio and a reactive microstructure. We show that the hierarchical structuring with micro- to nanoscale features results in a device with markedly increased photocatalytic activity as compared with a solid unstructured catalyst surface. This is evidenced by the successful degradation of persistent aqueous contaminants, sulfamethoxazole, and polystyrene microplastics. The design can potentially be implemented with solar photocatalysts in flow-through water purification systems.